2021
DOI: 10.3390/ijerph182010666
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Ageing and Aerobic Exercise

Abstract: Impairment of vascular function, in particular endothelial dysfunction and large elastic artery stiffening, represents a major link between ageing and cardiovascular risk. Clinical and experimental studies identified numerous mechanisms responsible for age-related decline of endothelial function and arterial compliance. Since most of these mechanisms are related to oxidative stress or low-grade inflammation, strategies that suppress oxidative stress and inflammation could be effective for preventing age-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 128 publications
(134 reference statements)
0
21
0
Order By: Relevance
“…The clinical improvement in functional status in the elderly driven by elevated physical activity or exercise performing could be contributed to by the beneficial impact produced by these lifestyle attitudes/interventions on cardiovascular system. Different studies have demonstrated the beneficial effects of exercise on both age-related endothelial dysfunction and arterial stiffening [ 245 ]. In this sense, preserved endothelial function in addition to a reduction in age-related arterial stiffness was observed in older subjects who underwent habitual aerobic exercise when compared to sedentary adults [ 246 , 247 ].…”
Section: Impact Of Physical Activity/exercise On Oxidative Stress And...mentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical improvement in functional status in the elderly driven by elevated physical activity or exercise performing could be contributed to by the beneficial impact produced by these lifestyle attitudes/interventions on cardiovascular system. Different studies have demonstrated the beneficial effects of exercise on both age-related endothelial dysfunction and arterial stiffening [ 245 ]. In this sense, preserved endothelial function in addition to a reduction in age-related arterial stiffness was observed in older subjects who underwent habitual aerobic exercise when compared to sedentary adults [ 246 , 247 ].…”
Section: Impact Of Physical Activity/exercise On Oxidative Stress And...mentioning
confidence: 99%
“…Available studies identified the diminution of oxidative stress and inflammation as possible mechanisms by which exercise may prevent and/or reverse endothelial dysfunction and arterial stiffness related to the aging process [ 245 ]. The above-mentioned benefits of exercise on lowering muscle oxidative stress and inflammation associated with aging might be extended to vascular tissue ( Figure 3 ).…”
Section: Impact Of Physical Activity/exercise On Oxidative Stress And...mentioning
confidence: 99%
“…Lifestyle factors and population characteristics were also correlated with alterations in aging. It is not surprising that aerobic activity was correlated with decreased BA, as it has been largely associated with protective effects on the body, including slowing vascular aging 27 and cognitive function 28 in the elderly. Because vigorous exercise is more closely associated to increases in muscle mass, it is possible that the greater glucose requirements for proper function pulls glucose from the blood to be metabolized in the skeletal muscle, therefore allowing for lower blood glucose and less risk of harmful effects on the rest of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, healthy ageing will contribute to reducing the risk and the severity of various diseases. For that, a healthy lifestyle that includes, in addition to exercise [ 137 , 138 , 139 ], sleep quality [ 140 ] and metal health [ 141 ], optimized diets choice is a key to achieve healthy ageing. Within this context, and based on the ageing-related pathways, mainly the oxidative stress [ 142 ] and redox regulation [ 143 ] involving reactive oxygen and nitrogen species [ 135 ] and free radicals [ 144 , 145 ], a diet of selected properties would contribute to healthy ageing.…”
Section: Diet and Calories-independent Patternsmentioning
confidence: 99%